From Advocacy to Indemnity: Rethinking Lawyers’ Fees as Elements of Civil Compensation - Ghansham Anand; Angelica Novia Walasondakh; Gwyneth Eugenia Keisya Howard (Jurnal Mulawarman Law Review, 2025)
Lawyers' fees often constitute a substantial economic burden for litigants, particularly for parties who perceive themselves as having suffered a violation of their rights due to another's conduct. In practice, there has been a growing tendency to demand the shifting of legal fees to the opposing party as part of a claim for damages in civil proceedings. However, Indonesian legislation has yet to provide explicit regulation on this matter. This legal lacuna has led to divergent judicial interpretations, resulting in a duality of views within judicial practice. This article seeks to analyse the legal standing of lawyers' fees within the framework of civil law as a compensable element of damages, and to identify the legal conditions under which the imposition of legal fees on the opposing party may be justified. Employing a normative juridical method with statutory, conceptual, case-based, and comparative approaches, this study finds that judicial opinions remain divided regarding the recognition of lawyers' fees as recoverable damages, and that no explicit procedural rule currently governs the shifting of such costs. By way of comparison, the article examines the American Rule and the English Rule on cost allocation to highlight contrasting paradigms in the treatment of legal fees. The analysis ultimately recommends the formulation of clearer norms, whether through judicial instruments such as a Supreme Court Circular or through legislative reform, in order to foster legal certainty and ensure the proportional and equitable protection of civil rights.